2015
DOI: 10.2319/030714-160.1
|View full text |Cite
|
Sign up to set email alerts
|

The premature loss of primary first molars: Space loss to molar occlusal relationships and facial patterns

Abstract: Objective: To investigate space changes with the premature loss of primary first molars and their relationship to permanent molar occlusion and facial forms. Materials and Methods: Two hundred twenty-six participants (ranging in age from 7 years 8 months to 8 years 2 months; 135 female, 91 male) met all inclusion criteria designed to study space loss as a result of the premature loss of the primary first molar. After 9 months, space loss was evaluated in relationship to molar occlusion and facial form. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 11 publications
1
42
0
1
Order By: Relevance
“…[ 6 ] Studies have shown that the premature loss of primary teeth is associated with the reduction of the dental arch length and migration of the marginal and antagonist teeth, leading to rotation, crowding, and impaction of the permanent teeth. [ 7 8 9 ] In addition, the reduction of the dental arch length is greater in the mandible than in the maxilla[ 10 11 ] if a primary second molar, rather than primary first molar, is lost. [ 12 ] In addition, this effect is also apparent if tooth loss occurs at an earlier age,[ 13 ] and if it occurs in crowded dentition as opposed to well-spaced dentition.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Studies have shown that the premature loss of primary teeth is associated with the reduction of the dental arch length and migration of the marginal and antagonist teeth, leading to rotation, crowding, and impaction of the permanent teeth. [ 7 8 9 ] In addition, the reduction of the dental arch length is greater in the mandible than in the maxilla[ 10 11 ] if a primary second molar, rather than primary first molar, is lost. [ 12 ] In addition, this effect is also apparent if tooth loss occurs at an earlier age,[ 13 ] and if it occurs in crowded dentition as opposed to well-spaced dentition.…”
Section: Introductionmentioning
confidence: 99%
“…Alexander expanded the study to examine the correla tion between the amount of space lost after extraction and molar relation and type of face [18]. Assessing the ratio of the length of the section determined by the skin points zygion to the section nasiongnathion, he distinguished the leptoprosopic face (ratio 0.75 or less), mesoprosopic face (ratio 0.760.79) and eurypro sopic face (ratio 0.8 or greater).…”
Section: Resultsmentioning
confidence: 99%
“…Increased susceptibility to dental caries of these teeth probably re sults from the specific anatomy of their occlusal surface characterized by deeper fossils and fissures and leads to their loss more frequently than in the case of earli er erupting first molars [26]. Summing up the findings from cited studies about the premature loss of first de ciduous molars, it can be assumed that a space maintain er should be considered in patients with an unerupted first permanent molar or cusptocusp contact, because mesial forces acting during permanent teeth eruption tend to accelerate space loss within the dental arch [18]. In addition, there is a greater risk of unfavorable spa tial changes in the lower arch, which may occur both as a result of the mesial migration of the posterior teeth and even more significant distal drift of the anterior teeth [19,27].…”
Section: Discussionmentioning
confidence: 99%
“…The American Academy of Pediatric Dentistry supports the insertion of space maintainers to replace first primary molars when permanent first molars are erupting (American Academy of Pediatric Dentistry, 2019). Also, it has been suggested that children with end-to-end molar occlusion and hyperdivergent facial biotype may be more susceptible to tooth migration (Alexander, Askari & Lewis, 2015).…”
Section: Discussionmentioning
confidence: 99%